The Role of Behavioral Biases on Stock Investment Decision of Youth Investors in Pokhara: Financial Literacy as a Moderator - Adhikari, Aastha; Kunwar, Kripa (Journal of Business and Management, 2025)
Background: Behavioral finance recognizes the effect of psychology and emotions in decision-making, in contrast with the concept of traditional finance that distorts the investor’s rationality, and hampers market efficiency.    Objectives: The purpose of the study is to investigate the impact of behavioral biases in investment decisions. It furthermore examines the moderating effect of financial literacy.  Methods: This study allowed the convenience sampling method and collects the data from 202 respondents using a structured questionnaire conducting a survey. Similarly, the multiple regression model was employed to examine the impact of behavioral biases in investment decisions and the moderating effect of financial literacy.Results: The study claimed that both overconfidence bias (β = .24, p < .001) and anchoring bias (β = .32, p < .001) have a positive impact, while herding behavior (β = -.20, p < .001) has a negative impact on investment decisions of youths. However, loss aversions (β = .05, p = .442) appear insignificant on investment decisions. In addition, this study established that financial literacy (β = -0.82, p < .05) moderates the relationship between overconfidence bias and investment decisions, effectively decreasing the effect of overconfidence bias.     Conclusions: Youth investors appear overconfident about their financial skills and self-judgments, as well as rely more on initial and outdated information in investment decisions-making. Likewise, investors who follow herd mentality would not be able to make informed decisions in the market. Additionally, financial literacy appeared as a strong moderator, which helps to reduce the negative impact of overconfidence bias on investment decisions.  This study enriches academic literature and offers significant implications to the stakeholders.